Core@shell strategies to enhance green upconversion emission of LaAlO3:ErIII, YbIII nanoparticles - Garcia, A. B.S. [UNESP]; Davolos, M. R. [UNESP]; Lima, S. A.M. [UNESP]; Pires, A. M. [UNESP] (Elsevier, 2024)
Seeking enhanced luminescence in upconverter nanoparticles, LAO:ErIII0.01, YbIII0.01, LAO = LaAlO3, with an average diameter of 30–40 nm, was synthesized via a modified Pechini method. Two coating strategies were employed: the first with three layers of 1 % LAO, and the second with LAO:NdIIIx at% (x = 10 or 30) or LAO:NdIIIx at%, YbIIIy at% (x, y = 30, 2 or 30, 20). Characterization included FTIR, UV–Vis diffuse reflectance, TEM, XRD, and photoluminescence. In the first strategy, undoped phase coating maintained the LaAlO3 rhombohedral crystalline structure, enhancing ErIII core emission under 980 nm laser excitation. In the second case, the shell containing YbIII (3 or 20 at%) under laser at 808 nm, favored the increase in the relative emission intensity of the activator, exciting ErIII directly in the core or via the outer NdIII sensitizer. Kinetic measurements fixing excitation at 980 nm and emission at 542.5 nm resulted in ErIII excited state decay values between 56 and 68 μs. The doped shell favored increased excited state lifetimes, exhibiting concentration quenching in the 30 % YbIII condition. Both NdIII presence and its combination with YbIII enhanced green emission compared to the uncoated core. From thermometric studies, the successive depositions of inert layers of LAO contributed to the highest relative thermal sensitivity of 1.79 % K−1 at 305 K, among the systems studied. Therefore, the core@shell strategies were successful in intensifying ErIII emission, both in the green and red regions, and resulted in relevant figures of merit that qualify them for applications in nanothermometry in the biological window.